Titanium alloy material adaptable to melt extrusion 3D printing forming process

A titanium alloy material with Ti-6Al-4V powder and a tailored binder system addresses the inefficiencies of existing 3D printing technologies, enabling cost-effective and stable production of complex titanium alloy parts through melt extrusion.

CN119140814AInactive Publication Date: 2024-12-17ZHEJIANG NORMAL UNIV
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202411650159.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-19
Publication Date
2024-12-17
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Current 3D printing technologies for metal materials, particularly those using titanium alloys, face challenges such as high equipment costs, low molding efficiency, and the need for additional heating sources, while existing solutions for metal binder melt extrusion primarily focus on stainless steel and lack effective methods for titanium alloys.

Method used

A titanium alloy material comprising Ti-6Al-4V powder and a polyoxymethylene-based binder, with specific proportions of high-density polyethylene, ethylene-vinyl acetate copolymer, stearic acid, and paraffin, is developed to ensure proper mixing and extrusion, avoiding phase separation and nozzle clogging, and maintaining shape stability during degreasing and sintering.

Benefits of technology

The titanium alloy material enables high-efficiency, low-cost production of complex titanium alloy parts with good dimensional stability and shape retention, suitable for continuous and batch production using melt extrusion 3D printing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119140814A_ABST
    Figure CN119140814A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of alloy materials, and particularly relates to a titanium alloy material capable of adapting to a melt extrusion 3D printing forming process. In order to solve the problem that in the prior art, a titanium alloy material is difficult to apply to melt extrusion 3D printing, the titanium alloy material capable of adapting to the melt extrusion 3D printing forming process is provided, the titanium alloy material comprises metal powder and a binder, the metal powder is Ti-6Al-4V powder, and the binder is a polyformaldehyde-based binder. The invention provides the material which takes the titanium alloy Ti-6Al-4V as the metal powder and is suitable for melt extrusion 3D printing forming, the good comprehensive performance of the titanium alloy is effectively introduced into the field of melt extrusion 3D printing forming, and the capital cost is greatly reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of alloy materials, and in particular relates to a titanium alloy material that can be adapted to a melt extrusion 3D printing molding process. Background Art

[0002] At present, the metal 3D printing market is developing rapidly, but most of the 3D printing technologies used for metal materials, such as selective laser sintering (SLS), selective laser melting (SLM), electron beam selective melting (EBSM), etc., have problems such as high equipment cost, low molding efficiency, the need for additional heating sources, and high rated power. The metal binder melt extrusion 3D printing molding process can effectively alleviate the above problems. It can achieve high-efficiency, low-cost batch production of complex parts, and can ensure certain precision requirements, verifying the rationality and feasibility of product design.

[0003] There are also related technical solutions in the prior art that use metal binder melt extrusion 3D printing molding process, but most of these technical solutions are for printing stainless steel parts, and there is no successful technical solution for 3D printing using titanium alloys. Titanium alloys generally have good comprehensive properties, such as high strength, good biocompatibility, corrosion resistance, etc., and are preferred materials in the fields of automobiles, medical treatment, aerospace, etc. Therefore, it is particularly important to provide a titanium alloy material that is suitable for 3D printing molding using titanium alloy as a metal raw material.

[0004] For example, a Chinese invention patent application discloses a 3D printing metal material [application number: 202010450402.7]. The invention application includes the following main components and the weight proportions of each component are: 30-40 parts of Al-Cu alloy, 25-35 parts of Al-Mn alloy, 20-30 parts of Si, 15-20 parts of Mg, 10-15 parts of Ni, 8-13 parts of Bi and 5-10 parts of Sn, and also includes the following auxiliary materials in weight proportions: 3-8 parts of sodium alginate and 2-6 parts of ethyl silicate. The method for preparing the 3D printing metal material comprises the following steps: step 1, raw material preparation: prepare the main material according to the above weight proportions, and treat the surface oil stains and oxide layer of the main material; step 2, mix the main material and sodium alginate and crush them by a crusher, and grind the crushed material by adding ethyl silicate into a grinder to obtain metal material powder; step 3, put the metal material powder into a smelting furnace, raise the temperature from 50-70 degrees to 800-950 degrees until the raw materials are all melted, and then keep warm for 1-2 hours to obtain alloy liquid; step 4 , control the temperature of the alloy liquid at 700-720 degrees, fill the smelting furnace with inert gas for degassing for 3-5 minutes, then add refining agent and heat it to 810-830 degrees for refining treatment to obtain a metal material solution; step five, cool the obtained metal material solution to 600-650 degrees, and form it into a die-casting part on a die-casting machine at an ultra-low speed injection speed of 0.1-0.2m / s; step six, cool the die-casting part to room temperature, and use a ball mill to grind the die-casting part into powder, and then dry the powder at low temperature to obtain a 3D printing metal material.

[0005] This invention application has the advantage of greatly refining the organizational properties of 3D printed metal materials, distributing them relatively evenly, and avoiding large internal defects of the printed products. However, it still does not solve the above-mentioned problems. Summary of the invention

[0006] The purpose of the present invention is to provide a titanium alloy material that can be adapted to the melt extrusion 3D printing molding process in order to solve the above problems.

[0007] In order to achieve the above object, the present invention adopts the following technical solutions: The titanium alloy material applicable to the melt extrusion 3D printing process comprises metal powder and a binder, wherein the metal powder is Ti-6Al-4V powder and the binder is a polyoxymethylene-based binder.

[0008] In the above-mentioned titanium alloy material that can be adapted to the melt extrusion 3D printing molding process, the Ti-6Al-4V powder includes 0.2-0.4% Fe by mass, 0.05-0.2% C by mass, 0.01-0.1% N by mass, 0.05-0.2% O by mass, 5.5-6.8% Al by mass, 3.5-4.5% V by mass and the balance Ti.

[0009] In the above-mentioned titanium alloy material that can be adapted to the melt extrusion 3D printing molding process, the Ti-6Al-4V powder includes 0.3% Fe by mass, 0.1% C by mass, 0.05% N by mass, 0.1% O by mass, 6.1% Al by mass, 4.0% V by mass and the balance Ti.

[0010] In the above-mentioned titanium alloy material adaptable to the melt extrusion 3D printing molding process, the binder includes 50-90 parts by mass of a main binder, 10-50 parts of a skeleton agent and 1-10 parts of an additive.

[0011] In the above-mentioned titanium alloy material adaptable to the melt extrusion 3D printing molding process, the main binder is polyoxymethylene, and the skeleton agent includes high-density polyethylene and ethylene-vinyl acetate copolymer.

[0012] In the above-mentioned titanium alloy material adaptable to the melt extrusion 3D printing molding process, the additives include a flow aid and a lubricant.

[0013] In the above-mentioned titanium alloy material that can be adapted to the melt extrusion 3D printing molding process, the flow aid is stearic acid and the lubricant is paraffin.

[0014] In the above-mentioned titanium alloy material that can be adapted to the melt extrusion 3D printing molding process, the binder includes 50-90 parts by mass of polyoxymethylene, 8-40 parts by mass of high-density polyethylene, 0.3-3 parts by mass of ethylene-vinyl acetate copolymer, 0.1-0.5 parts by mass of stearic acid and 0.7-7 parts by mass of paraffin.

[0015] The main binder is POM (polyoxymethylene). As the main component, POM has a low degree of polymerization and low viscosity, which can make the printed titanium alloy material have good fluidity, so that it can be stably extruded from the nozzle for blank printing during the printing process; at the same time, POM has a certain polarity and can fully contact the surface of the metal powder to avoid two-phase separation. The degreasing method corresponding to the polyoxymethylene binder system is "catalytic degreasing + thermal degreasing". POM will be completely removed during the catalytic degreasing process, so it is necessary to add high-melting-point components as skeleton agents to maintain the shape of the degreased blank. Therefore, HDPE (high-density polyethylene) and EVA (ethylene-vinyl acetate copolymer) were selected as skeleton agents respectively. First, the decomposition temperature of HDPE and EVA is relatively high, which can maintain the shape of the degreased blank after catalytic degreasing; secondly, multiple skeleton agents can be gradually removed without destroying the shape of the green blank in a short time. SA (stearic acid) is selected as a flow aid to make the surface of the metal powder and the binder more closely bonded, prevent the separation of the two phases, and ensure uniform mixing. Finally, adding PW (paraffin wax) as a lubricant can improve the fluidity of the feed, make the mixing and extrusion process smoother, and avoid nozzle clogging.

[0016] As the main filler, its mass proportion is the largest; as skeleton agents, HDPE and EVA should not be too large in proportion to avoid carbon and oxygen residues; SA, as a weak acid, will cause POM to gradually decompose during heating, so the proportion of SA should be small, preferably less than 1% of the total mass of the binder; PW, as a lubricant, can effectively improve the fluidity of the feed, but too high fluidity will cause the two phases of metal powder and binder to separate, so the content of PW should not be too high. Taking all the above into consideration, the mass fractions of each component of the final selected binder are as above.

[0017] In the above-mentioned titanium alloy material that can be adapted to the melt extrusion 3D printing molding process, the powder loading amount of the metal powder is 55-59%, wherein the percentage of the volume of the metal powder to the volume of the binder is defined as the powder loading amount.

[0018] Theoretically, the higher the metal powder ratio, the better. The higher the metal powder ratio, the less residual binder after sintering and the higher the density of the parts. However, the applicant found through practice that based on fused deposition modeling, the material must have a certain fluidity in order to print successfully.

[0019] The applicant has found through experiments that if the binder content in titanium alloy materials is too high, it will be distributed in the gaps between metal powders. The metal powders are relatively dispersed, with only a few leaning against each other, and most of them do not achieve point contact. Metal powders tend to agglomerate, and too much binder will cause metal powder segregation during the mixing process. During degreasing and sintering, a large amount of binder components will be lost. After the binder is removed, the particles cannot remain in their original position and may even collapse. In addition, too much binder will increase the sintering shrinkage rate, and there will be more carbon and oxygen residues in the sintered part, which will make the size of the parts difficult to control, and impurities will be introduced to affect the mechanical properties. In contrast, when there is an excess of metal powder, too little binder will lead to the formation of pores, making molding difficult. During the degreasing process, these pores will cause cracks. In addition, too little binder will cause the powder to not be fully wrapped, the adhesion between the powders will be insufficient, and the material strength will be reduced, thereby affecting the 3D printing performance of the material. In summary, too much or too little binder is not desirable, and the most ideal state is the critical state, that is, the metal powder particles are tightly stacked without the action of external force, the binder fills the gaps between the powders, and the metal powders are evenly wrapped. Therefore, the preparation of metal binder melt extrusion 3D printing titanium alloy materials requires a reasonable ratio of binder and metal powder, and the mixing is sufficient and uniform without too many pores. It should be noted that in the actual operation process, when the metal powder is in close contact, the powder has limited space for movement during extrusion, and the viscosity may be too high. Therefore, in actual operation, the powder loading selected in the experiment must be slightly less than the critical solid powder content of the powder.

[0020] The critical powder loading refers to the powder loading when the binder fills all the powder gaps. The formula for calculating the critical powder loading is: Φ = (ρ 振 / ρ)×100%; Where Φ is the critical powder loading (%), ρ 振 is the tap density of the metal powder (g / cm 3 ), ρ is the theoretical density of metal powder (g / cm 3 ).

[0021] The tap density of the powder is 2.7 g / cm 3 , the theoretical density is 4.51 g / cm 3 , it can be calculated that Φ=59.8%, and the powder loading amount selected in the experiment must be slightly smaller than the critical solid powder content of the powder, so the powder loading amount selected by the applicant is in the range of 55%-59%.

[0022] In the above-mentioned titanium alloy material that can be adapted to the melt extrusion 3D printing molding process, the metal powder is a coarse-grained powder or a fine-grained powder, and the average particle sizes of the fine-grained powder: D10, D50 and D90 are 5.50 μm, 12.29 μm and 20.82 μm respectively; the average particle sizes of the coarse-grained powder: D10, D50 and D90 are 22.75 μm, 40.04 μm and 53.51 μm respectively.

[0023] When preparing the titanium alloy material: The adhesive components are mixed in the above proportions and poured into a mixer for uniform mixing. The mixed adhesive components are then melted and extruded by a single screw extruder and pelletized to obtain adhesive particles. The temperature from the feed port to the extruder head is set to 160°C, 175°C, 185°C, 190°C and 195°C, and the screw speed is 80 rpm. Finally, the adhesive feed is obtained.

[0024] The premixed binder particles and metal powder were manually premixed according to the proportion and placed in the twin-screw feeder. The twin-screw temperature was set to 165°C, 175°C, 185°C, 190°C, 195°C, 200°C and 195°C from the feed port to the extruder head, and the screw speed was 120 rpm. The metal powder and binder were extruded through the twin-screw and then passed through a pelletizer to obtain metal binder particles. The particles were placed in an oven and dried at 80°C for 4 hours before being taken out.

[0025] The dried metal binder particles can be directly used for fused deposition modeling or further made into wires with standard diameters (1.75mm or 2.85mm) for fused deposition modeling. The single screw extruder for preparing the wire sets the temperature range at 165~200℃ and the screw speed at 80 rpm. The wire passes through the conveying cooling mechanism and the size measuring mechanism. After being completely cooled, it is transferred to the wire winding machine to obtain the final titanium alloy wire.

[0026] Compared with the prior art, the advantages of the present invention are: The titanium alloy Ti-6Al-4V material provided by the present invention can be melt-extruded like thermoplastics, and is suitable for continuous and batch production; at the same time, the particles or wires made of the material have good fused deposition modeling 3D printing performance, the printed parts have good dimensional stability, and can maintain good shape stability and low deformation during degreasing and sintering. In addition, the present invention provides a method for low-cost production of complex-shaped titanium alloy parts by means of fused deposition modeling 3D printing technology. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 The cross-sectional SEM images of the titanium alloy materials prepared in Example 3 and Example 6; Figure 2 Surface scanning electron microscope images of the titanium alloy materials prepared in Example 3 and Example 6; DETAILED DESCRIPTION

[0028] The present invention will be further described in detail below with reference to the accompanying drawings and specific implementation methods.

[0029] Example 1 This embodiment provides a titanium alloy material that can be adapted to a melt extrusion 3D printing molding process, including Ti-6Al-4V metal powder and a binder, wherein the powder loading amount of the Ti-6Al-4V metal powder is 55%.

[0030] The Ti-6Al-4V metal powder includes 0.2% by mass of Fe, 0.05% by mass of C, 0.01% by mass of N, 0.05% by mass of O, 5.5% by mass of Al, 3.5% by mass of V and the balance of Ti.

[0031] The particle size distribution D10, D50 and D90 of the metal powder are 22.75 μm, 40.04 μm and 53.51 μm, respectively.

[0032] The binder includes 50 parts by weight of polyoxymethylene, 40 parts by weight of high-density polyethylene, 3 parts by weight of ethylene-vinyl acetate copolymer, 0.5 parts by weight of stearic acid and 7 parts by weight of paraffin wax.

[0033] Example 2 This embodiment provides a titanium alloy material that can be adapted to a melt extrusion 3D printing molding process, including Ti-6Al-4V metal powder and a binder, wherein the powder loading amount of the Ti-6Al-4V metal powder is 59%.

[0034] The Ti-6Al-4V metal powder includes 0.4% by mass of Fe, 0.2% by mass of C, 0.1% by mass of N, 0.2% by mass of O, 6.8% by mass of Al, 4.5% by mass of V and the balance of Ti.

[0035] The particle size distribution D10, D50 and D90 of the metal powder are 22.75 μm, 40.04 μm and 53.51 μm, respectively.

[0036] The binder includes 90 parts by weight of polyoxymethylene, 8 parts by weight of high-density polyethylene, 0.3 parts by weight of ethylene-vinyl acetate copolymer, 0.1 parts by weight of stearic acid and 0.7 parts by weight of paraffin.

[0037] Example 3 This embodiment provides a titanium alloy material that can be adapted to a melt extrusion 3D printing molding process, including Ti-6Al-4V metal powder and a binder, wherein the powder loading amount of the Ti-6Al-4V metal powder is 57%.

[0038] The Ti-6Al-4V metal powder includes 0.3% by mass of Fe, 0.1% by mass of C, 0.05% by mass of N, 0.1% by mass of O, 6.1% by mass of Al, 4.0% by mass of V and the balance of Ti.

[0039] The particle size distribution D10, D50 and D90 of the metal powder are 22.75 μm, 40.04 μm and 53.51 μm, respectively.

[0040] The binder includes 85 parts by weight of polyoxymethylene, 10 parts by weight of high-density polyethylene, 3 parts by weight of ethylene-vinyl acetate copolymer, 0.5 parts by weight of stearic acid and 1.5 parts by weight of paraffin.

[0041] Example 4 This embodiment provides a titanium alloy material that can be adapted to a melt extrusion 3D printing molding process, including Ti-6Al-4V metal powder and a binder, wherein the powder loading amount of the Ti-6Al-4V metal powder is 55%.

[0042] The Ti-6Al-4V metal powder includes 0.2% by mass of Fe, 0.05% by mass of C, 0.01% by mass of N, 0.05% by mass of O, 5.5% by mass of Al, 3.5% by mass of V and the balance of Ti.

[0043] The particle size distribution D10, D50 and D90 of the metal powder are 5.50 μm, 12.29 μm and 20.82 μm, respectively.

[0044] The binder includes 50 parts by weight of polyoxymethylene, 40 parts by weight of high-density polyethylene, 10 parts by weight of ethylene-vinyl acetate copolymer, 3 parts by weight of stearic acid and 7 parts by weight of paraffin.

[0045] Example 5 This embodiment provides a titanium alloy material that can be adapted to a melt extrusion 3D printing molding process, including Ti-6Al-4V metal powder and a binder, wherein the powder loading amount of the Ti-6Al-4V metal powder is 59%.

[0046] The Ti-6Al-4V metal powder includes 0.4% by mass of Fe, 0.2% by mass of C, 0.1% by mass of N, 0.2% by mass of O, 6.8% by mass of Al, 4.5% by mass of V and the balance of Ti.

[0047] The particle size distribution D10, D50 and D90 of the metal powder are 5.50 μm, 12.29 μm and 20.82 μm, respectively.

[0048] The binder includes 90 parts by weight of polyoxymethylene, 8 parts by weight of high-density polyethylene, 2 parts by weight of ethylene-vinyl acetate copolymer, 0.3 parts by weight of stearic acid and 0.7 parts by weight of paraffin.

[0049] Example 6 This embodiment provides a titanium alloy material that can be adapted to a melt extrusion 3D printing molding process, including Ti-6Al-4V metal powder and a binder, wherein the powder loading amount of the Ti-6Al-4V metal powder is 57%.

[0050] The Ti-6Al-4V metal powder includes 0.3% by mass of Fe, 0.1% by mass of C, 0.05% by mass of N, 0.1% by mass of O, 6.1% by mass of Al, 4.0% by mass of V and the balance of Ti.

[0051] The particle size distribution D10, D50 and D90 of the metal powder are 5.50 μm, 12.29 μm and 20.82 μm, respectively.

[0052] The binder includes 85 parts by weight of polyoxymethylene, 10 parts by weight of high-density polyethylene, 3 parts by weight of ethylene-vinyl acetate copolymer, 0.5 parts by weight of stearic acid and 1.5 parts by weight of paraffin.

[0053] Application Example 1 Combination Figure 1 and Figure 2 As shown, Figure 1 (a) and (b) are cross-sectional scanning electron micrographs of the titanium alloy material prepared in Example 3, and (c) and (d) are cross-sectional scanning electron micrographs of the titanium alloy material prepared in Example 6; Figure 2 (a) and (b) are surface scanning electron microscope images of the titanium alloy material prepared in Example 3, and (c) and (d) are surface scanning electron microscope images of the titanium alloy material prepared in Example 6.

[0054] As can be seen from the figure, the powder filling inside the fine powder particle titanium alloy material is relatively tighter, the powders are in close contact with each other, and no obvious pores and agglomerations are produced. The dents in the figure are caused by the powder falling off after brittle fracture; in addition, it can be found that the surface of the titanium alloy material made of coarse metal powder has some tiny pores, while the surface of the titanium alloy material made of fine metal powder is obviously much smoother and has no obvious defects. However, the surfaces of the two titanium alloy materials are relatively smooth, the metal powder distribution in the two titanium alloy materials is relatively uniform, and the internal binder also fully wraps the metal powder. It can be seen that both can be adapted to the melt extrusion 3D printing molding process, achieving the intended purpose of the present invention.

[0055] The specific embodiments described herein are merely examples of the spirit of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in similar ways, but they will not deviate from the spirit of the present invention or exceed the scope defined by the appended claims.

Claims

1. Titanium alloy material suitable for melt extrusion 3D printing molding process, including metal powder and binder, characterized in that: The metal powder is Ti-6Al-4V powder, and the binder is a polyoxymethylene-based binder.

2. The titanium alloy material applicable to the melt extrusion 3D printing molding process as claimed in claim 1, characterized in that: The Ti-6Al-4V powder comprises 0.2-0.4% by mass of Fe, 0.05-0.2% by mass of C, 0.01-0.1% by mass of N, 0.05-0.2% by mass of O, 5.5-6.8% by mass of Al, 3.5-4.5% by mass of V and the balance of Ti.

3. The titanium alloy material applicable to the melt extrusion 3D printing molding process as claimed in claim 2, characterized in that: The Ti-6Al-4V powder includes 0.3% by mass of Fe, 0.1% by mass of C, 0.05% by mass of N, 0.1% by mass of O, 6.1% by mass of Al, 4.0% by mass of V and the balance of Ti.

4. The titanium alloy material applicable to the melt extrusion 3D printing molding process as claimed in claim 1, characterized in that: The binder comprises 50-90 parts by weight of a main binder, 10-50 parts by weight of a framework agent and 1-10 parts by weight of an additive.

5. The titanium alloy material applicable to the melt extrusion 3D printing molding process as claimed in claim 4, characterized in that: The main binder is polyoxymethylene, and the skeleton agent includes high-density polyethylene and ethylene-vinyl acetate copolymer.

6. The titanium alloy material applicable to the melt extrusion 3D printing process as claimed in claim 4, characterized in that: The additives include flow aids and lubricants.

7. The titanium alloy material applicable to the melt extrusion 3D printing molding process as claimed in claim 6, characterized in that: The flow-aiding agent is stearic acid, and the lubricant is paraffin.

8. The titanium alloy material applicable to the melt extrusion 3D printing molding process as claimed in claim 4, characterized in that: The binder comprises 85 parts by weight of polyoxymethylene, 10 parts by weight of high-density polyethylene, 3 parts by weight of ethylene-vinyl acetate copolymer, 0.5 parts by weight of stearic acid and 1.5 parts by weight of paraffin.

9. The titanium alloy material applicable to the melt extrusion 3D printing molding process according to claim 1, characterized in that: The powder loading amount of the metal powder is 55-59%, wherein the powder loading amount is defined as the percentage of the volume of the metal powder to the volume of the binder.

10. The titanium alloy material applicable to the melt extrusion 3D printing process according to claim 1, characterized in that: The metal powder is a coarse-grained powder or a fine-grained powder. The average particle sizes of the fine-grained powder: D10, D50 and D90 are 5.50 μm, 12.29 μm and 20.82 μm respectively; the average particle sizes of the coarse-grained powder: D10, D50 and D90 are 22.75 μm, 40.04 μm and 53.51 μm respectively.

Citation Information

Patent Citations

  • 3D printing metal material

    CN111534709A

  • 3D printing additive manufacturing method of Ti6Al4V injection molding feedstock

    CN106984819A

  • Ti-6Al-4V alloy feed for powder injection molding and preparation method of Ti-6Al-4V alloy feed

    CN108326282A

  • Method for preparing cobalt-based alloy complex parts by adopting powder injection molding

    CN111250709A

  • Titanium alloy extrusion type indirect 3D printing method

    CN111283184A